Interaction between IL-33 Gene Polymorphisms and Current Smoking with Susceptibility to Systemic Lupus Erythematosus. (11th March 2019) - Zhu, Xiaohua; Xie, Lin; Qin, Haihong; Liang, Jun; Yang, Yongsheng; Xu, Jinhua; Zhang, Tiejun
Abstract : Aims . This study is aimed at exploring the relation between IL-33 single-nucleotide polymorphisms (SNPs) and the risk of systemic lupus erythematosus (SLE). Methods . SNPStats (online software) was used to test the Hardy-Weinberg equilibrium in controls. Generalized multifactor dimensionality reduction (GMDR) was adopted to screen the preferable interaction between IL-33 SNPs and current smoking. Results . Logistic regression analysis based on the fundamental data of age, gender, BMI, current smoking, and alcohol drinking showed that both rs1929992-G and rs1891385-C alleles were correlated with an increasing risk of SLE, the ORs (95% CI) of which were 1.62 (1.21-2.05) and 1.64 (1.22-2.10), respectively. One two-locus model ( rs1929992 ×current smoking) had a testing accuracy of 60.11% (P = 0.0010 ). Through an overall multidimensional model, optimum cross-validation consistency was obtained. The analysis indicated that current smoking status influenced the SLE risk depending on the genotypes at rs1929992 . Pairwise LD analysis indicated that haplotype rs1929992G-rs7044343T was statistically related to the elevating risk of SLE (P < 0.05 ). Those subjects with the G-T haplotype had a higher SLE risk than those with other haplotypes, after correction with factors, including gender, alcohol drinking, age, BMI, and current smoking. Conclusions . The rs1929992-G and rs1891385-C allele, interaction between the rs1929992 gene and current smoking, and haplotype rs1929992G-rs7044343T were all risk factors of SLE.